Development of Low Cost Supernumerary Robotic Fingers as an Assistive Device - Mochammad Ariyanto; Rifky Ismail; Joga Dharma Setiawan; Zainal Arifin (Proceeding of the Electrical Engineering Computer Science and Informatics, 2017)
This paper presents the development of new type of wearable robot namely Supernumerary Robotic Finger (SRF) as  an  assistive   robot  for  healthy  people  or  people   with hemiparesis or hemiplegia. SRF comprises of two manipulators attached  in user’s wrist. Three flex sensors are utilized to measure the finger bending of the user’s finger. The posture of SRF is driven by modified glove sensor. The kinematics of both robotic thumb (RT) and robotic finger (RF) is studied using D-H parameter method and RoboAnalyzer software in order to understand the kinematic behavior of this robot. Each of RT and RF has three degrees of freedom (DOF). The posture of RT and RF is controlled using bending angles of thumb and finger from the user that are read by flex sensor. Based on the experimental results for people with healthy hand, the proposed SRF can assist object manipulation task in grasping, holding, and manipulating an object by using single hand when normally it only can be done by using two hands. From the experimental results on a person with healthy hand, the proposed of SRF can be employed as an assistive device for people with hemiparesis or hemiplegia. This device will enable people with diminished hand function work more independently.